The synergy of dietary supplements Lactobacillus salivarius LI01 and Bifidobacterium longum TC01 in alleviating liver failure in rats treated with d-galactosamine. Issue 20 (21st September 2021) - Zhuge, Aoxiang; Li, Shengjie; Yuan, Yin; Li, Bo; Li, Lanjuan
Abstract : L. salivarius LI01 and B. longum TC01 synergize in liver injury via altering gut microbiota and protecting gut barrier. Abstract : Lactobacillus salivarius ( L. salivarius ) has been widely used in dietary supplements and clinical treatments. Previous studies demonstrated the protective effect of L. salivarius LI01 on liver injury induced by d -galactosamine (d -GaIN) in rats. Accumulating evidence indicates that Lactobacillus and Bifidobacterium are highly coordinated; so in this study, we focus on the synergistic effect of L. salivarius LI01 and B. longum TC01 on the alleviation of liver injury caused by d -GaIN in rats and aim to find out the underlying interaction between the two strains. We observed reduced hepatic damage in the d -GaIN-treated rats with probiotic pre-administration, characterized by lower levels of AST and ALT ( p < 0.05) and decreased HAI (Histological Activity Index) scores. Moreover, cotreatment with LI01 and TC01 more effectively decreases proinflammatory cytokines TNF-α, MCP-1 and M-CSF ( p < 0.05) so as to inhibit systemic inflammation. Gut barrier dysfunction was ameliorated with compound probiotic pretreatment, as evidenced by the ultrastructure integrity, decreased histological score and elevated TJP-1 expression. What's more, supplementation with LI01 and TC01 markedly alleviates gut dysbiosis in the G-DaIN-treated rats, with enrichment of short chain fatty acid (SCFA) producers Faecalibaculum and Eubacterium_xylanophilum_ group, a decreased Firmicutes / Bacteroidetes (F/B) ratio and depletion of proinflammatory microbes, such as Peptococcaeae and Ruminococcaceae_UCG-005 . This study highlights the synergistic effect of dietary supplements LI01 and TC01 on the protection against liver failure, which is probably via altering gut microbiota.